Effect of IT Mindfulness Enhancement Program in Reducing Technostress in Media Agency Employees - Intapunya, Dew; Priya Mohan, Kanu (Journal of Behavioral Science for Development, 2024)
The current study aimed to examine the effectiveness of the IT mindfulness program among media agency employees by measuring mean scores of IT mindfulness, technostress, employee well-being, and job satisfaction before and after joining the program. The researcher developed the program by integrating literature on IT mindfulness and its elements consisting of the alertness to distinction (AD), the awareness of multiple perspectives (AP), and the openness to novelty (ON) incorporating the Mindfulness Experiential Learning Theory. Participants were 30 media agency employees purposefully selected to join the intervention program. Data were analyzed with SEM. The results showed that the mean scores of IT mindfulness and employee well-being of the experimental group after joining the program were significantly higher than before joining the program (d = -.56, p < .05) and (d = -.39, p < .05), respectively. The mean score of technostress of the experimental group after joining the program was significantly lower than before joining the program (d = .59, p < .05). Learning from the current program could benefit heavy-tech organizations and their employees. The content of the program could be applied to mitigate technostress and increase employee well-being in organizations.